Implementasi Tahsin Al-Qur’an Berbasis Fonologi Majlis Taklim Nurul Khasanah Desa Simpang Limbur Merangin - Suci Rahayu; Susilawati Susilawati; Ari Diana; Muhibul Fahmi; Sri Utaminingsih (PT. Meja Ilmiah Publikasi, 2026)
This community service article describes the implementation of tahsin Surah Al-Fatihah through a phonological approach aimed at improving the accuracy of Qur’anic recitation. The activity was conducted at MT. Nurul Khasanah RT 01 with fiveteen participants who were actively involved in Qur’anic learning. Using a descriptive qualitative approach, data were collected through observation, recitation practice, and documentation. The phonological approach focused on articulatory accuracy, sound differentiation, and pronunciation awareness according to makhraj and sifat al-huruf. The results show that threeteen out of fiveteen participants experienced significant improvement in their recitation accuracy after the tahsin session, particularly in vowel length, consonant articulation, and sound clarity. This program demonstrates that integrating phonological principles into tahsin activities effectively enhances Qur’anic reading quality and linguistic awareness among participants.